2016
DOI: 10.1007/s00702-016-1623-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute doses of methylphenidate on inflammation and oxidative stress in isolated hippocampus and cerebral cortex of adult rats

Abstract: Methylphenidate (MPH) is a stimulatory agent in brain with unknown long-term consequences. In this study, MPH-induced neurodegeneration in adult rat brain was assessed. Rats were acutely treated with different doses of MPH. Open Field Test was used to investigate anxiety and depression levels. Inflammatory factors and anti-oxidant activity were also evaluated in isolated hippocampus and cerebral cortex. MPH treated groups (10 and 20 mg/kg) demonstrated anxiety and depression like behavior in OFT. MPH significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Furthermore, an increase in oxidative stress was shown with acute and chronic MPH treatment in the SHR [ 78 ]. Finally, acute administration of high doses of MPH in adult rats produced oxidative damage, reduced GSH, SOD, GPx, and glutathione reductase (GR) activities, and provoked neurodegeneration in the cerebral cortex and hippocampus [ 79 ]. Recently, in the cortex and hippocampus of rats treated with MPH, MDA levels were increased and SOD levels reduced [ 81 ].…”
Section: Role Of Oxidative Stressmentioning
confidence: 99%
“…Furthermore, an increase in oxidative stress was shown with acute and chronic MPH treatment in the SHR [ 78 ]. Finally, acute administration of high doses of MPH in adult rats produced oxidative damage, reduced GSH, SOD, GPx, and glutathione reductase (GR) activities, and provoked neurodegeneration in the cerebral cortex and hippocampus [ 79 ]. Recently, in the cortex and hippocampus of rats treated with MPH, MDA levels were increased and SOD levels reduced [ 81 ].…”
Section: Role Of Oxidative Stressmentioning
confidence: 99%
“…One study showed that acute and chronic treatment with MPH in the SHR model increased oxidative stress [136]. Finally, the acute administration of high doses of MPH can cause oxidative and inflammatory changes in brain cells and induce neurodegeneration in the hippocampus and cerebral cortex of adult rats [137].…”
Section: Oxidative Stress and The Relationship With Adhdmentioning
confidence: 99%
“…Accordingly, elevation of NO production together with increased ROS might not only have positive effects, as peroxynitrite is an extremely potent oxidative species [59]. In fact, it was shown that MPH triggers ROS production in various animal studies [60,61]. By contrast, a clinical study points to protective effects of MPH against oxidative stress, at least after 12 weeks of MPH medication [62].…”
Section: Blood Pressure In Pediatric Adhd and Potential Effects Of Mphmentioning
confidence: 99%